2009
DOI: 10.1097/cad.0b013e32832d1149
|View full text |Cite
|
Sign up to set email alerts
|

Isoquercitrin isolated from Hyptis fasciculata reduces glioblastoma cell proliferation and changes β-catenin cellular localization

Abstract: Isoquercitrin isolated from the aerial parts of Hyptis fasciculata was evaluated according to its capacity to interfere with glioblastoma (Gbm) cell growth. Gbm cells were incubated with isoquercitrin, quercetin, or rutin at concentrations of 25, 50, and 100 mumol/l for 24, 48, and 72 h. Quercetin and rutin affected Gbm cell proliferation after treatment times of longer than 24 h. However, increasing concentrations of isoquercitrin inhibited 50% of Gbm cell proliferation at 24 h and further reached nearly 90% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
53
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 40 publications
4
53
0
1
Order By: Relevance
“…Our previous study suggested that isoquercitrin changes ␤-catenin cellular localization (16). To test this hypothesis, we conducted a siamois reporter assay (S01234-Lux) for the Wnt/␤-catenin pathway in Xenopus embryos (23).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study suggested that isoquercitrin changes ␤-catenin cellular localization (16). To test this hypothesis, we conducted a siamois reporter assay (S01234-Lux) for the Wnt/␤-catenin pathway in Xenopus embryos (23).…”
Section: Resultsmentioning
confidence: 99%
“…These anti-proliferative effects were accompanied by changes in ␤-catenin cellular localization, suggesting that Wnt/␤-catenin signaling might be altered by this flavonoid (16).…”
mentioning
confidence: 95%
See 3 more Smart Citations